2016
DOI: 10.1002/pbc.26207
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and analgesic effects of methadone in children and adults with sickle cell disease

Abstract: Background Vaso-occlusive episodes (VOE) are a significant source of morbidity among children and adults with sickle cell disease (SCD). There is little information on methadone use for SCD pain. This investigation evaluated methadone pharmacokinetics in children and adults with SCD, with a secondary aim to assess pain relief and opioid consumption. Procedure Participants included children (<18 yr) and adults with a VOE requiring hospitalization. Patients were randomly assigned to receive standard care (opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Methadone taken orally is subjected to an important first‐pass effect and is detectable in the plasma about 30 minutes after administration . Its bioavailability varies from 41–76% to 85–95% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methadone taken orally is subjected to an important first‐pass effect and is detectable in the plasma about 30 minutes after administration . Its bioavailability varies from 41–76% to 85–95% .…”
Section: Discussionmentioning
confidence: 99%
“…25 Methadone taken orally is subjected to an important first-pass effect and is detectable in the plasma about 30 minutes after administration. 26,27 Its bioavailability varies from 41-76% to 85-95%. 28,29 In our study, co-administration with isavuconazole, ketoconazole and voriconazole, the main pharmacokinetic parameters of methadone changed more or less.…”
Section: Discussionmentioning
confidence: 99%
“…Routes of administration can include oral, rectal, nasal, sublingual, subcutaneous, epidural or intravenous [ 6 ]. The half-life of methadone varies significantly between individuals and over time, and is shorter in children, [ 7 , 8 , 9 ]. With chronic administration the half-life in adults drops from 54.8 h to 24 h [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study did not identify a difference in pain response between short and long acting opioids but was not focused on the impact of methadone on decreasing healthcare utilization among patients with SCD experiencing chronic pain . For acute pain benefit, a single dose of intravenous (IV) methadone was recently shown to have improved pain scores when used in addition to standard of care pain relief strategies in hospitalized children and adult patients with SCD …”
Section: Introductionmentioning
confidence: 99%
“…6 For acute pain benefit, a single dose of intravenous (IV) methadone was recently shown to have improved pain scores when used in addition to standard of care pain relief strategies in hospitalized children and adult patients with SCD. 7 There are concerns for methadone use worth noting, including prolongation of the QTc interval. A Finnish toxicity study identified patients treated with methadone having the highest fatal toxicity index.…”
Section: Introductionmentioning
confidence: 99%